Early patients' illness perception as a predictor of post-traumatic stress disorder and quality of life one month after mild traumatic brain injury: a prospective study - Mulyadi, Mulyadi; Sithichoksakulchai, Siriluk; Gannika, Lenny; Sembiring , Erika Emnina (Jurnal Ners, 2024)
Introduction: The illness perception of mild Traumatic Brain Injury (mTBI) patients before discharge from the hospital tends to be inappropriate. Apart from that, post-injury symptoms such as post-traumatic stress disorder (PTSD) are often experienced by patients, which can affect their quality of life. However, research linking patient perceptions with post-traumatic stress and quality of life remains scarce. This study aimed to examine patient's illness perceptions and their relationship with PTSD and HRQOL. Methods: This study employed a prospective survey. Illness perceptions were measured before hospital discharge, and a follow-up of post-traumatic stress and health-related quality of life using an online survey was conducted one month later. The survey was administered from July to October 2023 at two hospitals, with a sample size of 72 mTBI patients. Results: mTBI patients with older age (p=.001), negative emotional perceptions (p=<.001), more consequence (p=.045), more concern about their injury (p=<.001) are significantly related to more symptoms of post-traumatic stress. Patients with mTBI who felt more identity symptoms of IR (p=.001), worsened personal control (p=.041), and worsened treatment control (p=.011) are significantly related to deteriorated quality of life one month after injury. Conclusions: This study produces evidence that mTBI patients' perceptions before leaving the hospital tend to be inappropriate and are related to post-traumatic stress and quality of life one month later. Based on these results, it is crucial for trauma nurses to identify patients' illness perceptions and initiate appropriate interventions to reduce PTSD symptoms and improve patients' quality of life.